Planejamento sucessório em empresas familiares : um estudo de caso em uma empresa do setor metal-mecânico do Espírito Santo - Silva, Caio Ruano da (2013)
The main goal of this dissertation is to investigate how the values of the entrepreneur family and the organizational culture affects the planning structure of the succession process in a family business group located in the Espírito Santo State. The data